2003
DOI: 10.1023/a:1021172200868
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In the quest for deciphering the neural code, theoretical advances were made which allow for the determination of the information rate inherent in the spike trains of nerve cells. However, up to now, the dependence of the information rate on stimulus parameters has not been studied in any neuron in a systematic way. Here, I investigate the information carried by the spike trains of H1, a motion-sensitive visual interneuron of the blowfly (Calliphora vicina) using a moving grating as a stimulus. Stimulus parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…On the basis of individual response traces, it is not easily possible to discern stimulus-driven activity changes from those that are due to sources not associated with the stimulus (“noise”). The origin of various potential noise sources in the visual motion pathway and the consequences of the unreliable nature of neural signals have been analysed in flies (e.g., de Ruyter van Steveninck and Bialek, 1995; de Ruyter van Steveninck et al, 1997; Warzecha and Egelhaaf, 1999; Warzecha et al, 2000; Egelhaaf et al, 2001; Lewen et al, 2001; Borst, 2003; Grewe et al, 2003, 2007; Nemenman et al, 2008). These aspects, as well as the impact of neuronal noise on the precision with which motion information can be encoded, have been controversially discussed (Haag and Borst, 1997, 1998; Warzecha and Egelhaaf, 1997; Warzecha et al, 1998, 2000, 2003; Brenner et al, 2000b; Fairhall et al, 2001; Kalb, 2006).…”
Section: Behavioral Significance Of Optic Flow Neuronsmentioning
confidence: 99%
“…On the basis of individual response traces, it is not easily possible to discern stimulus-driven activity changes from those that are due to sources not associated with the stimulus (“noise”). The origin of various potential noise sources in the visual motion pathway and the consequences of the unreliable nature of neural signals have been analysed in flies (e.g., de Ruyter van Steveninck and Bialek, 1995; de Ruyter van Steveninck et al, 1997; Warzecha and Egelhaaf, 1999; Warzecha et al, 2000; Egelhaaf et al, 2001; Lewen et al, 2001; Borst, 2003; Grewe et al, 2003, 2007; Nemenman et al, 2008). These aspects, as well as the impact of neuronal noise on the precision with which motion information can be encoded, have been controversially discussed (Haag and Borst, 1997, 1998; Warzecha and Egelhaaf, 1997; Warzecha et al, 1998, 2000, 2003; Brenner et al, 2000b; Fairhall et al, 2001; Kalb, 2006).…”
Section: Behavioral Significance Of Optic Flow Neuronsmentioning
confidence: 99%
“…Moreover, at low light intensities, the combination of the discrete nature of light and the high sensitivity of the photoreceptors introduces noise into the system, which seems to be responsible for around 50% of the noise measured in the response of postsynaptic cells [12]. The consequences of this noise further downstream the visual pathway are still being debated [13][17].…”
Section: Introductionmentioning
confidence: 99%
“…The first experiments addressing this point were performed, again on the fly visual system using the motion-sensitive neuron H1, by Brenner et al (2000), later confirmed and extended by Fairhall et al (2001) and Borst (2003). In all the three studies, flies were stimulated with a rigidly moving spatial pattern.…”
Section: Resultsmentioning
confidence: 90%
“…Here, instead of the method reported in Brenner et al (2000), Fairhall et al 2001 andBorst (2003), the immediate responses of both the model and the fly neuron are displayed. In order to have comparable output signals, the model response was fed into a leaky integrate-and-fire neuron.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation